Cambodia : Third Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2001)
Economic developments and policy implementation through mid-2001 were broadly consistent with the program. The authorities have started the participatory process that will underlie the full Poverty Reduction Strategy Paper. Civil service reform is critical to improve the delivery of public services and to ensure the medium-term viability of the fiscal program. The IMF staff welcomed the implementation of the first round of tariff restructuring that has reduced the number of tariff bands to four, and the maximum tariff rate to 35 percent.